The essential Naguib Mahfouz - Maḥfūẓ, Najīb, 1911-2006 (American University in Cairo Press, 2011)
Naguib Mahfouz, the first and only writer of Arabic to be awarded the Nobel prize for literature, wrote prolifically from the 1930s until shortly before his death in 2006, in a variety of genres: novels, short stories, plays, screenplays, a regular weekly newspaper column, and in later life his intensely brief and evocative Dreams. His Cairo Trilogy achieved the status of a world classic, and the Swedish Academy of Letters in awarding him the 1988 Nobel prize for literature noted that Mahfouz "through works rich in nuance-now clear-sightedly realistic, now evocatively ambiguous-has formed an A